IMPLEMENTATIONOFTOURISMDEVELOPMENTPOLICIESINCREOAND AGRO-TOURISMDESTINATIONS - Anjar Astuti; Dyah Lituhayu (Journal of Public Policy and Management Review, 2021)
Theproblem oftourism inthecityofSemarangistheinadequatedevelopmentand developmentoftourism destinationsandthelowqualityoffacilitiesandinfrastructure tosupporttourism activitiesinthecityofSemarang.Thepurposeofthisstudyisto determinetheimplementationoftourism developmentpoliciesincreativeandagrotourism destinationsandtodeterminethefactorsthathindertheimplementationof tourism developmentpoliciesincreoandagro-tourism destinations.Theresearch methodusedinthisresearchisdescriptivequalitativemethod.Theresultsofthisstudy indicatethattheimplementationoftourism developmentpoliciesincreoandagrotourism destinationsisstillnotmaximallyimplemented.Theavailabilityofpublic facilities,publicinfrastructureandtourism facilitiesisnotyetfullyavailable.The implementingorganizationintheimplementationofthispolicyconsistsofvarious partiesandthesocial,economic,andpoliticalconditionsaresufficienttohelpthelives ofthepeoplearoundthecreoandagro-tourism destinations,buttheyarestillnot optimallyimplemented.Factorsthathindertheimplementationoftourismdevelopment policiesincreoandagro-tourism destinationsarecommunicationintheform of overlappingunderstandingsbetweenpolicyimplementers,resourcesintheform of limitedfundsandnotmaximizedresourcesofattractionincreoandagro-tourism destinations,obstructionofthelicensingprocessdueto convolutedbureaucratic conditions,andnotyetThereisaclearstandardoperatingprocedureregardingthe implementationoftourismdevelopment.